Inhibitory Effect of Piceatannol on Streptococcus suis Infection Both in vitro and in vivo - Wang, Guizhen; Gao, Yawen; Wu, Xiuhua; Gao, Xiue; Zhang, Min; Liu, Hongmei; Fang, Tianqi (Frontiers in Microbiology, 2020)
Suilysin (SLY) plays a critical role in Streptococcus suis infections making it an ideal target to combat infection caused by this pathogen. In the present study, we found that piceatannol (PN), a natural compound, inhibits pore-formation by blocking the oligomerization of SLY without affecting the growth of S. suis and the expression of SLY. Furthermore, PN alleviated the J774 cell damage and the expression of the inflammatory cytokine TNF-α and IL-1β induced by S. suis in vitro. The computational biology and biochemistry results indicated that PN binds to the joint region of D2 and D4 in SLY, and Asn57, Pro58, Pro59, Glu76, Ile379, Glu380, and Glu418 were critical residues involved in the binding. The binding effect between PN and SLY hindered the SLY monomers from forming the oligomers, thereby weakening the haemolytic activity of SLY. This mechanism was also verified by analysis of haemolysis analysis and KA formation after site-specific mutagenesis. Furthermore, PN protected mice from S. suis infections by reducing bacterial colony formation and the inflammatory response in target organs in vivo. These results indicate that PN is a feasible drug candidate to combat S. suis infections.